Costos de obra y su influencia en la rentabilidad de la empresa constructora Sin Fronteras Consultores y Ejecutores S.A.C. – 2018 - Sanchez Quiroz, Coraima del Pilar (2021)
The present study was carried out with the objective of determining the influence of construction costs on the profitability of the construction company Sin Fronteras Consultores y Ejecutores S.A.C. in 2018. The type of study used is non-experimental, causal correlational design, and cross-sectional. Likewise, the applied research methods were descriptive and analytical. We worked with the same population and sample, represented by the company Constructora Sin Fronteras Consultores y Ejecutores S.A.C. For data collection, the technique of documentary analysis, the interview and the survey was used, whose instruments were the analysis of the document guide, the interview guide and the questionnaire, respectively. The information analysis has been carried out using descriptive and inferential statistics, as tools for data processing the Microsoft Excel 2016 program and the statistical software SPSS, version 25 were used. The results obtained from the Pearson's Chi-square statistical test show that construction costs significantly influence the profitability of the construction company Sin Fronteras Consultores y Ejecutores S.A.C., 2018, contrasting the research hypothesis, because the p_value was 0.029 less than 0.05, evaluated at 95% confidence, determining that the profitability of the work of Chugay 3 Km is 31.29%, Curgos 4.2 Km is 21.46%, Cachicadán 5 Km is 22.94%, a comparison was made of the profitability determined in the study and that projected by the company when making its estimate, finding differences of 0.50%, 13.35% and 9.97%in the works of Chugay, Curgos and Cachicadán respectively. The company's labor cost was determined considering the direct labor costs, direct materials and indirect manufacturing costs for each of the works carried out.